Association of Maternal Autoimmune Diseases With Risk of Mental Disorders in Offspring in Denmark - He Hua; Yu Yongfu; Liew Zeyan; Gissler Mika; Laszlo Krisztina D.; Valdimarsdottir Unnur Anna; Zhang Jun; Li Fei; Li Jiong (AMER MEDICAL ASSOC, 2022)
IMPORTANCE Maternal immune activation during pregnancy is associated with increased risks of several mental disorders in offspring during childhood, but little is known about how maternal autoimmune diseases during pregnancy are associated with mental health in offspring during and after childhood.
OBJECTIVE To investigate the association between maternal autoimmune diseases before childbirth and risk of mental disorders among offspring up to early adulthood.
DESIGN, SETTING, AND PARTICIPANTS This population-based nationwide cohort study used data from Danish national registers on singletons born in Denmark from 1978 to 2015 with up to 38 years of follow-up. Data analyses were conducted from March 1, 2020, through September 30, 2021.
EXPOSURES Maternal autoimmune disease diagnosed before or during pregnancy according to the Danish National Patient Register.
MAIN OUTCOMES AND MEASURES The main outcome was mental disorders, defined by hospital diagnoses, in offspring. Cox proportional hazards regression was used to estimate hazard ratios (HRs) and 95% CIs for mental disorders.
RESULTS Of the 2 254 234 singleton infants included in the study (median age, 16.7 years [IQR, 10.5-21.7 years]; 51.28% male), 2.26% were born to mothers with autoimmune diseases before childbirth. Exposed participants had an increased risk of overall mental disorders compared with their unexposed counterparts (HR, 1.16; 95% CI, 1.13-1.19; incidence, 9.38 vs 7.91 per 1000 person-years). Increased risks of overall mental disorders in offspring were seen in different age groups for type 1 diabetes (1-5 years: HR, 1.35 [95% CI, 1.17-1.57]; 6-18 years: HR, 1.24 [95% CI, 1.15-1.33]; >18 years: HR, 1.19 [95% CI, 1.09-1.30]) and rheumatoid arthritis (1-5 years: HR, 1.42 [95% CI, 1.16-1.74]; 6-18 years: HR, 1.19 [95% CI, 1.05436]; >18 years: HR, 1.28 [95% CI, 1.02-1.60]). Regarding specific mental disorders, increased risk after exposure to any maternal autoimmune disorder was observed for organic disorders (HR, 1.54; 95% CI, 1.21-1.94), schizophrenia (HR, 1.35; 95% CI, 1.21-1.51), obsessive-compulsive disorder (HR, 1.42; 95% CI, 1.24-1.63), mood disorders (HR, 1.12; 95% CI, 1.04-121), and a series of neurodevelopmental disorders (eg, childhood autism [HR, 1.21; 95% CI, 1.08436] and attention-deficit/hyperactivity disorder [HR, 1.19; 95% CI, 1.12-1.26]).
CONCLUSIONS AND RELEVANCE In this cohort study in Denmark, prenatal exposure to maternal autoimmune diseases was associated with increased risks of overall and type-specific mental disorders in offspring. Maternal type 1 diabetes and rheumatoid arthritis during pregnancy were associated with offspring's mental health up to early adulthood. Individuals prenatally exposed to autoimmune disease may benefit from long-term surveillance for mental disorders.